The fruit of Crataegus pinnatifida ameliorates memory deficits in β-amyloid protein-induced Alzheimer's disease mouse model. (28th October 2019) - Lee, Jihye; Cho, Eunbi; Kwon, Huiyoung; Jeon, Jieun; Jung, Chul Jong; Moon, Minho; Jun, Mira; Lee, Young Choon; Kim, Dong Hyun; Jung, Ji Wook
Abstract: Ethnopharmacological relevance: The fruit of Crataegus pinnatifida is a traditional medicine widely used as digestive drug in East Asia. Although Chinese herbal medicine used it for mental health, scientific evidence does not exist, yet. Aims of study: The aim of this study is to show that the ethanol extract of the fruit of Crataegus pinnatifida (CPE) has neuroprotective effect on Alzheimer' disease model mice. Materials and methods: Intracerebroventricular injection of Aβ was used to induce Alzheimer's disease-like pathology. Passive avoidance and Y-maze tasks were used to examine the effect of CPE on memory impairments by Aβ. Immunohistochemistry was used to examine the effect of CPE on glial activation. ThT assay was used to observe the effect of CPE on Aβ aggregation. MTT and LDH release assays were utilized to examine effects of CPE on Aβ-induced cytotoxicity. Results: CPE prevented memory deficit in Aβ-induced memory impairment model. Moreover, CPE prevented glial activation in the hippocampus of Aβ-injected model. In in vitro test, CPE inhibited Aβ fibril formation in a concentration-dependent manner. CPE also caused disaggregation of Aβ fibrils. Along with this, CPE blocked neuronal cell death induced by Aβ. Conclusions: Collectively, these experimental findings demonstrated that CPE could be a candidate for development of AD therapy. Graphical abstract: Image 1